Circulating Endothelial Progenitor Cells in Hypertensive Patients With Increased Arterial Stiffness. Issue 4 (19th March 2014) - Marketou, Maria E.; Kalyva, Athanasia; Parthenakis, Fragiskos I.; Pontikoglou, Charalampos; Maragkoudakis, Spyros; Kontaraki, Joanna E.; Chlouverakis, Gregory; Zacharis, Evangelos A.; Patrianakos, Alexandros; Papadaki, Helen A.; Vardas, Panos E.
<x xml:space="preserve">Abstract</x> The potential association between arterial stiffening and circulating endothelial progenitor cells (EPCs) in patients with essential hypertension was investigated. Pulse wave velocity (PWV) was used to evaluate arterial stiffness in 24 patients with essential hypertension and 19 healthy controls. Blood samples were taken and immunostained with antibodies against the cell surface markers CD34, CD45, and CD133. Using flow cytometry, EPCs as a population of CD45−/CD34+/CD133+ cells were measured. Hypertensive patients were not found to have higher levels of circulating CD45−/CD34+/CD133+ compared with the control group (0.0026%±0.0031% vs 0.0023%±0.0023%, respectively; P=.7). Correlation analysis revealed a strong association between the number of CD45−/CD34+/CD133+ cells and PWV (r=0.58, P<.001), indicating that hypertensive patients with increased PWV have a greater percentage of CD45−/CD34+/CD133+ cells. Data showed a correlation between the number of circulating CD45−/CD34+/CD133+ cells and arterial stiffness, suggesting that those cells might have a role in arterial remodeling.